2011
DOI: 10.1007/s00125-010-2030-3
|View full text |Cite|
|
Sign up to set email alerts
|

Risk stratification systems for diabetic foot ulcers: a systematic review

Abstract: Aims/hypothesis Several risk stratification systems have been proposed for predicting development of diabetic foot ulcer. However, little has been published that assesses their similarities and disparities, diagnostic accuracy and evidence level. Consequently, we conducted a systematic review of the existing stratification systems. Methods We searched the MEDLINE database for studies (published until April 2010) describing the creation and validation of risk stratification systems for prediction of diabetic fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
115
0
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(135 citation statements)
references
References 26 publications
10
115
0
10
Order By: Relevance
“…Visual acuity 76 (poor vision) score [10] and VPT score [12] (measure of neu-77 ropathy level) were reported to be associated with DFU. monly used predicting the risk of ulceration [14]. Recently 86 another systematic review and meta-analysis, reported that 87 insensitivity to a 10-g monofilament or one absent pedal 88 pulse will identify patients with moderate or intermediate 89 risk of foot ulceration [15].…”
mentioning
confidence: 99%
“…Visual acuity 76 (poor vision) score [10] and VPT score [12] (measure of neu-77 ropathy level) were reported to be associated with DFU. monly used predicting the risk of ulceration [14]. Recently 86 another systematic review and meta-analysis, reported that 87 insensitivity to a 10-g monofilament or one absent pedal 88 pulse will identify patients with moderate or intermediate 89 risk of foot ulceration [15].…”
mentioning
confidence: 99%
“…In this issue of Diabetologia, Dr Monteiro-Soares et al [1] have produced a timely systematic review of systems that have been described for classifying the relative risk of future ulceration of the foot in diabetic individuals. Disease of the foot represents a considerable threat-a threat to both the well-being and survival of the individual [2]-as well as posing an enormous burden on heathcare services.…”
mentioning
confidence: 99%
“…The formal studies cited by Monteiro-Soares et al [1] used a variety of methods to determine both neuropathy (loss of protective sensation) and peripheral arterial disease, and yet the conclusion from all was the same. Thus, it probably matters little that some of these definitive studies used equipment that is not in general use in the community (such as a biothesiometer) or that that there is no consensus on the choice or number of sites to be tested with, for example, a 10 g monofilament.…”
mentioning
confidence: 99%
“…11,12 Several diabetic foot ulcer risk stratification tools have been developed over the years wherein a systematic review by Monteiro-Soares et al, reveals the following: International Working Group on Diabetic Foot (IWGDF), University of Texas Foot Risk Stratification (UTFRS), Scottish Intercollegiate Guideline Network (SIGN), American Diabetes Association (ADA) and a tool developed by Boyko et al 12,13 Of all these tools, only Boyko et al, examined predictive validity through an external system wherein HbA1c is considered as a predictive variable. 12,13 However, predictive validity is highly examined in the tool developed by Inlow, wherein various researches examined the reliability and validity of the tool. [15][16][17][18][19] Hence, the Inlow's sixty second tool is found to be highly reliable for risk stratification of diabetic foot ulcers.…”
Section: Introductionmentioning
confidence: 99%